Editor's Choice – Long-term Survival and Risk Analysis in 136 Consecutive Patients With Type B Aortic Dissection Presenting to a Single Centre Over an 11 Year Period. (May 2019) - Clough, Rachel E.; Barillà, David; Delsart, Pascal; Ledieu, Guillaume; Spear, Rafaelle; Crichton, Siobhan; Mounier Vehier, Claire; Peacock, Janet; Sobocinski, Jonathan; Haulon, Stephan
Abstract : Objectives: To evaluate, in patients with acute type B aortic dissection, the results of medical and endovascular treatment in a large single centre experience and to investigate the clinical and imaging features on presentation that relate to poor outcome. Methods: This was a retrospective analysis of prospectively collected clinical and CT imaging data. Consecutive patients (136) with acute type B aortic dissection were included in the study over an 11 year period. The characteristics of patients receiving endovascular (complicated) or medical treatment (uncomplicated) were compared. Kaplan–Meier estimators were used to estimate cumulative overall survival and survival free of aortic events. Factors associated with overall and aortic event free survival were also explored using Cox proportional hazards models. Results: The mean follow up was 51 months (1–132), during which time 33 deaths and 48 aortic events occurred. At one and five years, overall survival was 94.0% and 74.8%, respectively, and freedom from aortic events was 75.6% and 58.7%. There was no difference in all cause survival and aortic event free survival at one and five years between the patients treated endovascularly and those receiving medical treatment alone. Risk analysis for aortic events demonstrated the maximum size of the proximal entry tear, the maximum thoracic aortic diameter, and the thoracic aortic false lumen maximum diameter to have a significant effect on the incidence of aortic events. Conclusions: Active management of patients with type B aortic dissection results in good long-term survival even in the presence of features traditionally associated with adverse outcomes. All patients require close lifetime surveillance as aortic events continue to occur during follow up even after endografting.